Beyond Disputes: A Study of Conflict Resolution Dynamics in Islamic Educational Institutions at Pesantren - Ahmad Hilman Halim; Jumarim Jumarim; Abdulloh Fuadi; Erwin Padli; Rizalul Khaer; Bq Ditia Widari; Muhammad Syawal Bin Sharizal (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study examines the dynamics of religious social conflict between At-Tadris Islamic Boarding School and the community of Bengkel Village, West Lombok. It aims to analyze the forms and causes of the conflict, the resolution process, and the transformation of post-conflict social relations within the context of Islamic education. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and document analysis, and analyzed using an interactive model. The findings reveal that the conflict evolved from a latent phase characterized by negative social perceptions of new religious practices into a manifest conflict triggered by the rapid spread of unverified information regarding an alleged assault on a religious teacher. The conflict was resolved through security measures, mediation, reconciliation (islah), and the active involvement of religious and community leaders, leading to the gradual restoration of social relations and broader community participation in pesantren activities. The novelty of this study lies in explaining religious social conflict as a dynamic process that develops from latent to manifest conflict and subsequently transforms into strengthened social relations through community-based reconciliation. Practically, the findings suggest that pesantren leaders should strengthen inclusive communication and actively involve local communities in religious and social activities to prevent misunderstandings and build mutual trust. The study also provides educational stakeholders and policymakers with insights for developing community-based conflict prevention and reconciliation strategies within Islamic educational institutions.